Overcoming Barriers to Successfully Commercializing Carbon Dioxide Utilization - Kant, Marvin (Frontiers in Energy Research, 2017)
The successful transition to a low-carbon economy hinges on innovative solutions and collaborative action on a global scale. Sustainable entrepreneurship is thereby recognized as a key driver in the creation and transformation of ecologically and socially sustainable economic systems. The purpose of this article is to contribute to this topic by understanding commercialization barriers for strong sustainability-oriented new technology ventures and to derive recommendations to overcome them. A qualitative multilevel approach is applied to identify barriers and drivers within the internal dynamic capabilities of the organization and within the organization’s external stakeholders. A model of barriers has been developed based on semi-structured interviews with new carbon dioxide utilization ventures and associated industry players in Canada, the USA, and the European Economic Area. Resulting recommendations to facilitate the (re-)design of a dedicated support system are proposed on four levels: (a) actors, (b) resources, (c) institutional settings, and (d) the coordination of the support system.